Exploring Business Opportunities in the Postponement of Debt Payment Obligations (PKPU) under Law No. 37 of 2004 on Bankruptcy - Nainggolan, Bernard (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2022)
This research aims to analyze three legal issues related to the provisions within Law No. 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations (UUK-PKPU), namely the short duration of the Postponement of Debt Payment Obligations (Penundaan Kewajiban Pembayaran Utang/PKPU) time limit, the provisions regarding time limit constraints as a cause of the failure of debtor's reconciliation efforts with creditors, and legal protection for the debtor's interests to prevent bankruptcy. This study adopts a normative juridical research method relying on secondary data and literature studies. This normative system includes principles, norms, regulations, court decisions, agreements, and doctrines that represent the views or teachings of legal scholars. The research findings indicate that PKPU aims to provide protection to creditors and offer debtors the opportunity to propose reconciliation regarding their debts. Although the time limit is not the determinant of the failure of reconciliation efforts, it does influence the achievement of the PKPU process. The debtor's weak bargaining position and the inability to reach an optimal reconciliation agreement are major concerns. UUK-PKPU provides legal protection for debtors, but the tight time limit may hinder the achievement of PKPU objectives. The implications of this research highlight the need for further review of PKPU time limit provisions to support the effectiveness of reconciliation efforts and protect debtor interests in avoiding bankruptcy.